Development of sensitive elements based on photochromic bacteriorhodopsin for fibre optic sensors - Korposh, Serhiy O. (Cranfield University, 2007)
This work focuses on the development of sensitive elements incorporating bacteriorhodopsin thin films for fibre optic sensors. The sensing principle is based on monitoring optical properties of the bacteriorhodopsin thin films during changes of environmental conditions. The photochromic properties of the bR films change in response to the presence of different chemical species and this effect can be employed for the development of sensitive elements for optical sensors. For practical sensing applications, one can monitor changes (in the presence of chemical species) of the spectral and kinetic parameters of bR films incorporated into a matrix. The main topic of this thesis is to study the possibility of using bacteriorhodopsin thin films for the construction of fibre-optic sensors for monitoring ammonia and humidity. The possibility to control sensitivity and selectivity of the sensor to the presence of ammonia and humidity by adding chemicals to the bR film and by employing different materials as a matrix for the creation of bR films is reported. The examples based on ammonia and relative humidity are used to show how using a broad range of different chemical additives bR can be sensitized to a wide spectrum of species, and thus possesses the potential to be a universal film material for optical sensors.